The Origin and Evolution of Chromosomal Reciprocal Translocation in Quasipaa boulengeri (Anura, Dicroglossidae) - Xia, Yun; Yuan, Xiuyun; Luo, Wei; Yuan, Siqi; Zeng, Xiaomao (Frontiers in Genetics, 2020)
Chromosomal rearrangements have long fascinated evolutionary biologists for being widely implicated in causing genetic differentiation. Suppressed recombination has been demonstrated in various species with inversion; however, there is controversy over whether such recombination suppression would facilitate divergence in reciprocal translocation with reduced fitness. In this study, we used the spiny frog, Quasipaa boulengeri, whose western Sichuan Basin populations exhibit translocation polymorphisms, to test whether the genetic markers on translocated (rearranged) or normal chromosomes have driven this genetic differentiation. We also investigated its overall genetic structure and the possibility of chromosomal fixation. Whole-chromosome painting and genetic structure clustering suggested a single origin of the translocation polymorphisms, and high-throughput sequencing of rearranged chromosomes isolated many markers with known localizations on chromosomes. Using these markers, distinct patterns of gene flow were found between rearranged and normal chromosomes. Genetic differentiation was only found in the translocated chromosomes, not in normal chromosomes or the mitochondrial genome. Hybrid unfitness cannot explain the genetic differentiation, as then the differentiation would be observed throughout the whole genome. Our results suggest that suppressed recombination drives genetic differentiation into a balanced chromosomal polymorphism. Mapping to a reference genome, we found that the region of genetic differentiation covered a wide range of translocated chromosomes, not only in the vicinity of chromosomal breakpoints. Our results imply that the suppressed recombination region could be extended by accumulation of repetitive sequences or capture of alleles that are adapted to the local environment, following the spread and/or fixation of chromosomal rearrangement.